2023
DOI: 10.3390/jcm12206540
|View full text |Cite
|
Sign up to set email alerts
|

Complete Blood Count Alterations Prior to the Diagnosis of Colorectal Cancer May Help in the Detection of Synchronous Liver Metastases

Rafael J. Sala,
John Ery,
David Cuesta-Peredo
et al.

Abstract: Background and Aims: Colorectal cancer (CRC) represents 10% of all cancers worldwide with the highest incidence in developed countries; its incidence is also increasing in middle- and low-income countries. Population screening programs facilitate early diagnosis of the disease. When the diagnosis is carried out in advanced stages, approximately 80% of patients with liver metastases (LM) are considered unresectable at the time of diagnosis. In our study, variations in blood counts prior to CRC diagnosis were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…This suggests that the induction of early-stage CRC and the dietary intervention with an OBG feed did not significantly alter these parameters. These results are consistent with research on patients with colorectal cancer, where changes in RBC parameters were found in the later stages of this cancer [ 57 ]. Based on a large meta-analysis, the authors suggest that RBC parameters, as well as WBC and platelet counts, can be used as predictors for referral to clinical testing for cancer diagnosis in the later stages of CRC [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the induction of early-stage CRC and the dietary intervention with an OBG feed did not significantly alter these parameters. These results are consistent with research on patients with colorectal cancer, where changes in RBC parameters were found in the later stages of this cancer [ 57 ]. Based on a large meta-analysis, the authors suggest that RBC parameters, as well as WBC and platelet counts, can be used as predictors for referral to clinical testing for cancer diagnosis in the later stages of CRC [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…In cancer, these biomarkers allow risk stratification in diagnosis and provide insight into the choice of therapy. Recent studies show that blood count changes occur months before diagnosis in patients with metastatic CRC compared to those without metastases [ 11 ]. Among the most commonly used biomarkers are hemoglobin, lymphocytes, neutrophils, and platelets.…”
Section: Introductionmentioning
confidence: 99%